“Life as Art”: Emerging Youth Networks in Hanoi and the Tree Hug Movement - Geertman, Stephanie; Boudreau, Julie Anne (John Wiley and Sons Inc., 2018)
Drawing on two years of fieldwork in Hanoi, this paper explores what it means to be young and politically engaged in a post-reform communist city that has recently integrated into the global economy and international culture. We suggest that many young people's desire to assert more playful urban lifestyles and to live their “lives as art” contributed to their engagement in the Tree Hug Movement that swept Hanoi in the spring of 2015. Using interviews with youth who were active in the Tree Hug Movement and ethnographic observations of how young people succeeded in “being” in public spaces, this paper suggests that play can easily transform into politics. Looking at the intertwinement of digital and physical urban spaces, we note how youth mobilized the Tree Hug Movement by drawing upon the same non-confrontational tactics that they first developed to carve out a space for themselves in urban public spaces: “quiet encroachment,” affective arguments, and conflict avoidance. This, we conclude, contributed to creating new forms of political engagement that can be observed elsewhere in the global urban world.
Keywords: Hanoi; Public Space; Tree Hug Movement; Wired Generation; Youth Movement; Geography, Planning and Development; Urban Studies